The Correlation between Family Socioeconomic Status and the Delayed Treatment of Retinoblastoma Patients at Dr. Soetomo General Hospital Surabaya - Naimatuningsih, Nanning; Soebagjo, Hendrian; Setiawati, Rosy; Loebis, Rozalina (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2019)
Introduction: Retinoblastoma is a cancer with the highest incidence in children and the second type of cancer that most often causes death in children in Indonesia. The level of delay in attending treatment for retinoblastoma patients in Dr. Soetomo General Hospital Surabaya is still high, because generally the patients come with an advanced stage, they are already in serious condition or with a poor prognosis. Treatment delay from the patients can be caused by the patients that are not feeling disturbed by the disease, not aware of the dangers of the disease, feel afraid, have no cost, the family does not allow them to see the doctor, and the health facilities are unaccessable. One of the factors that influence decision making whether or not someone comes to seek treatment is their socioeconomic status. The aim of this research is to analyze the correlation between family socioeconomic status with the delayed treatment for retinoblastoma patients at Dr. Soetomo General Hospital Surabaya.Methods: This research used observational analytic cross-sectional study. This research was conducted with the help of 33 retinoblastoma patients and families of retinoblastoma patients in the Outpatient Unit of the Poli Onkologi Satu Atap (POSA) Mata at Dr. Soetomo General Hospital Surabaya, and was taken by total sampling.Results: The results were obtained from 33 samples, 18.2% of patients came with a good prognosis, and 81.8% of patients came with a poor prognosis. The Fisher's Exact Test analysis (α = 0.05) was used to determine the correlation between the father's educational level and the delayed treatment of retinoblastoma patients (p = 0.322), correlation between the mother's educational level and the delayed treatment of retinoblastoma patients (p = 0.129), correlation between the father's level of occupation and the delayed treatment of retinoblastoma patients (p = 0.028), correlation between the mother's occupational level and the delayed treatment of retinoblastoma patients (p = 0.640), correlation between the family income level and the delayed treatment of retinoblastoma patients (p = 0.026).Conclusion: There were significant correlation between father's occupational level and family income level with the delayed treatment of retinoblastoma patients. Meanwhile there were no significant correlation between father's educational level, mother's educational level, and mother's occupational level with the delayed treatment of retinoblastoma patients.